Estimación de la huella de carbono de la empresa Heincke S.A.S. BIC (2023)
The anthropogenic emission of greenhouse gases (GHG) into the Earth's atmosphere is the main cause of the increase in global temperature and the imbalance of the climate system, which generate serious negative effects on the planet and all its inhabitants. Such a situation requires a great collective effort to reduce the generation and emission of GHG, where companies are key actors since they emit a considerable amount of GHG directly and indirectly. Reducing this impact starts from quantifying its emissions, also called carbon footprint. Therefore, the main objective of this degree project was to estimate the carbon footprint of the Colombian company Heincke S.A.S. BIC, dedicated to providing agricultural food supply services. For this, the GHG Protocol methodology was used, therefore, initially the evaluation of the company was delimited in an organizational, operational, and temporal manner, from which the emission sources were identified, continuing with the selection of the emission factors, the collection of activity data and the quantification of associated emissions. This exercise resulted in a total carbon footprint of 307,22 t CO2 eq, which is mainly based on Scope 3 (indirect emissions) and is the basis of the proposed measures to reduce emissions.